Suppose that f(5) = -1, f'(5) = 2, g(5) = 5, g'(5)=-3

find (g/(f^2+g))' (5).

I must be doing something wrong. Because my answer is way off. Or maybe it's because I'm not understanding the notation properly.

Printable View

- Sep 20th 2010, 11:17 AMpewpew01Math functions of functions.
Suppose that f(5) = -1, f'(5) = 2, g(5) = 5, g'(5)=-3

find (g/(f^2+g))' (5).

I must be doing something wrong. Because my answer is way off. Or maybe it's because I'm not understanding the notation properly. - Sep 20th 2010, 11:28 AMskeeter
- Sep 20th 2010, 11:33 AMpewpew01
Oh... right. Chain rule and quotient. How could I forget about it.

kk thanks.